Emerging oral Treponema membrane proteins disorder neutrophil phosphoinositide signaling via phosphatidylinositol-4-phosphate 5-kinase - Anselmi, Natalie K.; Vanyo, Stephen T.; Visser, Michelle B. (Frontiers in Oral Health, 2025)
BackgroundPeriodontitis (PD) is a group of inflammatory pathologies characterized by destruction of the tooth-supporting tissues. During PD, dysbiosis of the oral biofilm disrupts the host immune response and supports growth of pathogenic bacteria including the spirochetes Treponema denticola (Td), T. maltophilum (Tm), and T. lecithinolyticum (Tl). The outer membrane protein of Td, Msp, perturbs the function of neutrophils by modulating phosphoinositide (PIP) signaling. While Tm and Tl have similar outer membrane proteins, MspA and MspTL respectively, little is known of how these proteins affect neutrophil function.MethodsThis study examines putative mechanisms by which T. maltophilum MspA and T. lecithinolyticum MspTL inhibit neutrophil chemotaxis. Murine bone marrow neutrophils were treated with recombinant MspA or MspTL protein. Protein phosphorylation was assessed via immunoblot, phosphate release by malachite green assay, and PTEN and SHIP phosphatase activity through immunoprecipitation, enzymatic assays, and chemical inhibition. PIP quantification was assessed by immunofluorescence microscopy and Mass ELISAs, while small GTPase activity was measured with G-Protein Activation Assays. Neutrophil F-actin localization was determined through immunofluorescence.ResultsMspA and MspTL increase phosphate release in neutrophils, but unlike Msp, they do not affect PTEN or SHIP activity, despite modulating cellular levels of multiple PIP species [PI(3,4)P2, PI(4,5)P2, and PIP3]. Overall, MspA and MspTL differentially affected the metabolism of individual PIP species, but both increased PI(4,5)P2 levels in a PIP5K-dependent manner. Downstream effects of disrupted PIP signaling included inhibition of Akt and Rac1 activation and increased cortical F-actin localization.ConclusionsUnderstanding distinct mechanistic relationships between novel Msp proteins and neutrophils provides important insight into how these understudied bacteria promote periodontitis progression.